Enrolling HIV-positive adolescents in mental health research: A case study reflecting on legal and ethical complexities - Woollett, N; Peter, J; Cluver, L; Brahmbhatt, H (Health and Medical Publishing Group, 2017)
Adolescents living with HIV are an emerging group in the global HIV/AIDS epidemic. Mental health in this population affects HIV care, treatment, consequential morbidity and secondary transmission. There is a paucity of research regarding these youth in South Africa (SA), partly because section 71 of the National Health Act of 2003 (NHA) requires parental or guardian's consent.To explore legal and ethical issues related to conducting adolescent mental health research in SA.After obtaining a High Court order permitting research on minors aged <18 years without prior parental or guardian's consent, we used qualitative and quantitative methods to interview adolescents in five clinics serving HIV-positive adolescents in Johannesburg.Our study enrolled 343 participants; 74% were orphaned and did not have legal guardians, 27% were symptomatic for depression, anxiety or post-traumatic stress disorder, 24% were suicidal, and almost 90% did not feel that they belonged in the family with which they lived. Without court intervention, most of the participants could not have participated in this research because parental consent was impossible to obtain. This case study argues for exceptions to the parental consent requirement, which excludes orphaned and vulnerable children and youth from research.Recommendations are made to promote ethical integrity in conducting mental health research with adolescents. A balance is needed between protecting adolescents from exploitation and permitting access to benefits of research. Requiring parental consent for all research does not necessarily give effect to policy. For the vast majority of SA HIV-positive adolescents, parental consent is not possible. Section 71 of the NHA ought to be amended to facilitate valuable and necessary research concerning HIV-positive orphan children and adolescents.